Virtual Patients in Ophthalmic Medical Education: 10.36351/pjo.v39i1.1566 - Malik, Tayyaba Gul (Pakistan Journal of Ophthalmology, 2022)
Sir William Osler’s said, “Medicine is learned by the bedside and not in the classroom” and that, “He who studies medicine without books, sails an uncharted sea, but he who studies medicine without patients does not go to sea at all.”1 There is no second opinion about that but we see that over the years, especially in Ophthalmology, there has been a shift towards day care procedures. There are few inpatients with shorter duration of hospital stay. We also find that the standard of safe delivery of medical and surgical facilities is also rising and critical patients are not allowed to be handled by the trainee residents. With overwhelming responsibilities, clinical teachers have very little time for the residents and in private training centers, there is scarcity of patient variety even in the outdoor, resulting in lack of exposure to variety of clinical problems. All these developments pose a huge challenge in the training of postgraduate trainees who have to take the charge of future ophthalmologists.